2001
DOI: 10.1054/bjoc.2000.1595
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of expression and allelotype of mismatch repair genes (hMLH1 and hMSH2) in bladder cancer

Abstract: Mutation of human homologues of DNA mismatch repair (MMR) genes in tumours has been shown to be associated with the phenomenon of microsatellite instability (MSI). Several studies have reported the occurrence of MSI in bladder cancer, but evidence of involvement of MMR genes in the pathogenesis of this cancer is still unclear. We therefore utilized quantitative immunohistochemical (IHC) image analysis and PCR-based allelotype analysis to determine hMLH1 and hMSH2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
(42 reference statements)
4
15
1
1
Order By: Relevance
“…hMSH2 and hMSH6 were immunodetected in the nuclei of cancer cells, a finding in line with what has been found by other authors (8, 10–13, 15) and the well‐known contribution of these proteins in recognition and repair of acquired DNA damage as members of the mismatch repair system (1). What is interesting is the higher percentages of negative immunoreactivity observed for both proteins in our series of UCs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…hMSH2 and hMSH6 were immunodetected in the nuclei of cancer cells, a finding in line with what has been found by other authors (8, 10–13, 15) and the well‐known contribution of these proteins in recognition and repair of acquired DNA damage as members of the mismatch repair system (1). What is interesting is the higher percentages of negative immunoreactivity observed for both proteins in our series of UCs.…”
Section: Discussionsupporting
confidence: 90%
“…What is interesting is the higher percentages of negative immunoreactivity observed for both proteins in our series of UCs. We found lack of hMSH2 and hMSH6 in 25.9% and 49.2% of the cases, respectively, percentages that are much higher than the 1.7% (13) and ∼4% (8, 10) described so far. The discrepancies in the results concerning the frequency of hMSH2 and hMSH6 immunonegativity in bladder cancer between the various studies may reflect the heterogeneity of the tumors studied with regard to stage and grade, differences in applied antibodies and techniques, as well as ethnic variations.…”
Section: Discussioncontrasting
confidence: 66%
“…To date, a series of studies have attempted to determine the expression of MMR proteins, mainly MSH2 and MLH1, in bladder cancer, the majority using IHC methods (17)(18)(19)(20)(21)(22)(23)(24). Only two previous studies have determined MMR mRNA levels in bladder cancer by qPCR analysis and even in a few series of clinical specimens with different percentages from IHC analysis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of MMR genes may present as an absence or reduction of MMR gene expression or microsatellite instability (MSI) phenotype (15)(16)(17). The protein expression levels of the hMSH2, hMLH1 and hMSH6 MMR genes have been detected in histopathological material of UCC specimens by immunohistochemistry (IHC) with controversial results (17)(18)(19)(20)(21)(22)(23)(24). There is little and insufficient literature concerning the expression of the mRNA of MMR genes in bladder cancer specimens (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Leach et al19 found that tumors with positive hMSH2 immunohistochemical expression appeared to have higher levels of expression than adjacent urothelium and suggested this as a marker for TCC detection. Both Jin et al20 and Kassem et al21 found reduced expression in a proportion of TCC. One significant limitation of these studies is that different classifications of normal and abnormal staining were used in each of the reports.…”
mentioning
confidence: 93%